The fullness of time temporalities of the fifteenth-century Low Countries - Champion, Matthew S. (University of Chicago Press, 2017)
"Contents " -- "List of Illustrations" -- "List of Abbreviations" -- "Introduction" -- "1. The Polyphony of Civic Time in Fifteenth-Century Leuven" -- "2. The Altarpiece of the Holy Sacrament: Making Time in Leuvenâs St. Peterâs Church" -- "3. Music, Time, and Devotion: Emotional Narratives at the Cathedral of Cambrai" -- "4. The Advent of the Lamb: Unfolding History and Liturgy in Fifteenth-Century Ghent" -- "5. Calendars and Chronology: Temporal Devotion in Fifteenth-Century Leuven" -- "6. Time for the Fasciculus temporum: Time, Text, and Vision in Early Print Culture" -- "Conclusion" -- "Acknowledgments" -- "Notes" -- "Bibliography".